Utilizing Recycled Polyethylene Terephthalate Waste in Geopolymer Concrete Applications - Suryanto, Andy; Antonius, .; Irmawaty, Rita (Engineering, Technology & Applied Science Research, 2025)
Concrete has experienced a marked increase in usage for road construction over the past decade, largely due to its durability. This study proposes an innovative method for producing eco-friendly and sustainable cement mortar, using municipal waste and industrial by-products. The study investigates the use of Polyethylene Terephthalate (PET) plastic waste as a fiber to enhance the mechanical characteristics of geopolymer concrete, which is based on Fly Ash (FA) and Rice Husk Ash (RHA). The investigation focused on the mechanical characteristics of geopolymer concrete, including its flexural and compressive strengths. The study incorporated four distinct geopolymer concrete mixtures containing PET plastic waste into the fly ash and rice husk ash-based geopolymer concrete: 0% PET plastic waste (SN), 0.25% PET plastic waste (SA), 0.50% PET plastic waste (SB), and 0.75% PET plastic waste. Using a 100 mm x 100 mm x 400 mm block for flexural strength testing and a 10 cm x 20 cm cylinder for compressive strength testing, the tests were conducted seven- and twenty-eight-days following air curing. The flexural test results indicated a decline in average flexural strength value with every 0.25% PET addition, reaching a 6.48% decrease. Compression testing revealed a negative correlation between the addition of PET and the compressive strength of the material. Specifically, an increase of 0.25% to 0.5% in the PET content resulted in an average reduction of 24.22% in compressive strength. Conversely, the compressive strength exhibited an increase of 10.91% between the 0.75% and 0.5% range of PET.